Częstochowa Journalists - Dzierżyńska-Mielczarek, Jolanta (Respectus Philologicus, 2013)
This article characterises a local journalist environment. The analysis was conducted on the example of Częstochowa—a city that is identified with the Pauline monastery of Jasna Góra by most Europeans. Symbolically, that identification seems reasonable, but Częstochowa is also an independent urban organism carrying out not only religious tasks. The Częstochowa journalist environment, along with local press, arose in the late 19th century. Because the city at that time had a population of only a few thousand residents and was under Russian occupation, the environment was represented by just several people, mostly originating from other cities or the Catholic clergy. Journalists in Częstochowa became a separate professional group between 1918 and 1939. Their number at that time did not exceed one hundred. They were decimated during World War II. In the People’s Republic of Poland, the Częstochowa journalists were deprived of their independence and forced to engage in numerous propaganda activities. The uniformisation of the press also caused a significant reduction on the part of the examined group, which from 1945–1989 numbered less than one hundred. Thanks to sociological research, we know that between 1989–2007, over 200 journalists worked in the Częstochowa media. In the overwhelming majority of cases, they performed their journalist work in a regular and systematic manner, receiving a salary that was their primary or only source of income.